Induction Characteristics of Two different Concentrations of propofol in Children undergoing Eye surgeries - Laiq, Nasreen; Khan, Muhammad Naeem; Khan, Shahid; Reddy, CVM (Journal of Postgraduate Medical Institute, 2011)
To compare the induction characteristics of two different concentrations of propfol (i.e. 1% and 2%) in children undergoin eye surgeries. This cross sectional comparative study was conducted at LV prasad Eye iInstitute Hyderabad India. Hudred consecutive patients of American society of Anaesthesiologist (ASA) groups of 50 each. Group A were given propofol 1% while patients in Group B were given propofol 2% for induction of anaesthesia and were maintained with 1% isoflurane and 60% nitrous oxide in oxygen. Induction characteristics were assessed and compared in two groups. Students t test and chi square test were applide. Propofol 1% and propofol 2% are equally effective and safe for induction of anaesthesia in children undergoing eye surgeries.